Cashless payment system and Covid-19 on the example of the Czech Republic - Otakar Schlossberger; Marcela Soldanová (Financial Internet Quarterly, 2022)
The paper deals with cashless payments during the pandemic situation caused by Covid-19. The aim of the paper will be to use the method of analysis and comparison of selected data to answer the following research question: Has the pandemic caused by Covid-19 contributed to increasing the share of non-cash payments? The authors base their research on the hypothesis that "the pandemic period had a significant impact on the development of cashless payments". From the performed research, the authors came to the conclusion that based on the methods used, the established hypothesis was not confirmed and the answer to the research question had to be given in the negative.
Keywords: E42; G21; K22; 330; payments instruments; noncash payments; transactions; payment services; financial market regulation